Effect of planting date on incidence and damage by Sesamia calamistis (Lepidoptera: Noctuidae) in maize in southern Benin - Adda, C.; Atachi, P.; Hell, K.; Korie, S.; Tamo, Manuele (Springer, 2009)
Stem and cob borers cause substantial damage to maize and affect the quality and economic value of maize in West Africa. Manipulation of planting dates is considered a possible mechanism for averting the overall impact of borers and their damage to the crop. Experiments were carried out in southern Benin to evaluate the effect of various planting dates on the incidence and damage to maize by Sesamia calamistis (Hampson). The trials were conducted at the Benin station of the International Institute of Tropical Agriculture (IITA) at Abomey-Calavi and at Sèhouè, located 70 km north of the IITA, Benin station. The planting dates were: early planting (the day following the first rains), intermediate planting (2–3 weeks after the early planting) and late planting (4–5 weeks after the early planting). The experiments were carried out in the main and minor cropping seasons, respectively, during two successive years in 2003 and 2004. The variables measured included population density of S. calamistis, percentage of infested plants and cob damage. In the main cropping season, incidence of stemborers and percentage of infested plants were higher in the late planting than in the early planting and intermediate planting treatments. The manipulation of planting dates for the control of S. calamistis during the minor maize growing season is not recommended.